A study to assess the perceived barriers in utilization of partograph - Sharma, Shivani; Parwez, Saroj; Batra, Kiran (International Journal Of Community Medicine And Public Health, 2022)
Background: Though maternal mortality can visualize the decreasing trends in India, but still we need to work hard for attaining sustainable development goals. As per the WHO, partograph must be used to monitor labor of all intra-natal mothers, but its implementation is limited due to various barriers experienced by health workers. The aim of the study was to assess the barriers which are experienced by the health care providers in actual utilization of the existing partograph. Methods:Qualitative research approach was adopted to understand the views related to the partograph. Interview techniques was adopted to collect data. Various focus group discussions were conducted from November 2018 to March 2019 to gather data related to barriers experienced by the partograph users in the hospital setting. The participants were from the health centres and educational institutions of Mohali and Patiala districts of Punjab. Results: Certain factors were highlighted in the discussion which needs to be addressed if we want that partograph should be used to its maximum potential. It brought to light various themes and factors which lead to underutilization of the existing partograph. The results highlighted the factors related to the partograph utilization, factors related to health centre, factors related to components of the partograph and enhancement of utilization of the partograph. Conclusions:It can be concluded that in developing countries like India, where we are still struggling with the maternal and child health issues, attention should be drawn to the actual problems faced by the health care providers so that maternal and perinatal outcomes can be improved.